2016
DOI: 10.1158/1078-0432.ccr-15-2170
|View full text |Cite
|
Sign up to set email alerts
|

TNF-Related Apoptosis-Inducing Ligand (TRAIL)–Armed Exosomes Deliver Proapoptotic Signals to Tumor Site

Abstract: Purpose: Exosomes deliver signals to target cells and could thus be exploited as an innovative therapeutic tool. We investigated the ability of membrane TRAIL-armed exosomes to deliver proapoptotic signals to cancer cells and mediate growth inhibition in different tumor models.Experimental Methods and Results: K562 cells, transduced with lentiviral human membrane TRAIL, were used for the production of TRAIL þ exosomes, which were studied by nanoparticle tracking analysis, cytofluorimetry, immunoelectronmicrosc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(131 citation statements)
references
References 50 publications
(55 reference statements)
5
120
0
Order By: Relevance
“…Induction of cell apoptosis is the main type of tumor treatment (7). Regulation of the intracellular redox state determines the cell's survival fate (8).…”
Section: Introductionmentioning
confidence: 99%
“…Induction of cell apoptosis is the main type of tumor treatment (7). Regulation of the intracellular redox state determines the cell's survival fate (8).…”
Section: Introductionmentioning
confidence: 99%
“…A group recently transduced k562 leukaemia cells with human TRAIL to create TRAIL+ secreted exosomes. In vitro TRAIL+ exosomes were found to induce apoptosis in melanoma and lymphoma cell lines [30]. In vivo, the exosomes homed to the site of the tumour with accumulation in the lungs, liver and spleen.…”
Section: Genetic Engineering Of Exosomesmentioning
confidence: 99%
“…In tumour bearing mice, it was found that the engineered exosomes induced necrosis and vessel damage in the myeloma and melanoma tumour groups, but no significant reduction in tumour volume was observed. However, the lymphoma group had a significant reduction of tumour growth when compared to the control groups [30]. It was suggested by the authors that the reasoning for the results observed were that only a fraction of the administered exosomes actually homed to the site of the tumour, with large amounts becoming trapped in major organs.…”
Section: Genetic Engineering Of Exosomesmentioning
confidence: 99%
“…Our unit has recently tested the efficacy of antitumor activity of exosomes originating from tumor necrosis factor-related apoptosis-inducing ligand (TRAIL)-transduced cells and carrying membrane TRAIL in preclinical studies [82]. Apart from targeting tumor cells, the proapoptotic activity of TRAIL exosomes could be exploited to limit immune suppression by eliminating TRAIL death receptor-expressing MDSCs [83].…”
Section: Evs As Conveyors Of Immune Suppression Therapeutic Vehicmentioning
confidence: 99%